(untitled) (Scientific journal of the Fergana State University, 2023)
We use mathematical concepts in studying the physics subject and analyzing the physical laws in secondary schools. From a historical point of view, we can see that mathematics has played a major role in development of physics. In this article we have analyzed the connectivity of physics and mathematics in secondary schools.